Wavelength dependence of optical nonlinearity of terpyridine-based Zn(II)-coordinated rigid linear polymers - He, Tingchao (2013)
We present the wavelength dependent optical nonlinearities of two terpyridine-based Zn(II)-coordinated rigid linear polymers. It is found that the polymers exhibit large saturable absorption behavior under resonant excitation, while strong and tunable 2-photon absorption behaviors are observed in the biological window of 700–900 nm. Interestingly, Z-scan results reveal that, the polymers also exhibit large positive nonlinear refraction at 1300 nm in the solutions even with a low concentration, accompanied by small 3-photon absorption. Our results suggest that the polymers will be promising in various photonic applications, such as mode locking, 2-photon biological imaging, and all-optical switching.